Water level prediction for rivers under tidal influence using artificial neural network - Rosmina, Binti Ahmad Bustami (Universiti Malaysia Sarawak, UNIMAS, 2005)
In this study, Artificial Neural Networks (ANN)s were developed to forecast water level for the next hour and the next 3,6 or 12 hours. The inputs consisted only of the rainfall, predicted tide level and previous water level. Backpropagation (BP) and recurrent (REC) network were selected for this study.